2021
DOI: 10.3390/info12080330
|View full text |Cite
|
Sign up to set email alerts
|

A Node Localization Algorithm for Wireless Sensor Networks Based on Virtual Partition and Distance Correction

Abstract: The coordinates of nodes are very important in the application of wireless sensor networks (WSN). The range-free localization algorithm is the best method to obtain the coordinates of sensor nodes at present. Range-free localization algorithm can be divided into two stages: distance estimation and coordinate calculation. For reduce the error in the distance estimation stage, a node localization algorithm for WSN based on virtual partition and distance correction (VP-DC) is proposed in this paper. In the distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, it was found that the localization error value decreased when we used the secure algorithm because of the authenticating mechanism used in the algorithm. Furthermore, the error value in the case of the basic DV-Hop was high in all cases compared to other algorithms, due to the usage of a distance error correction factor in the other algorithms [39]. Table 9 shows the average localization error variation corresponding to the total node number with and without malicious nodes for the proposed algorithm and other variants.…”
Section: Impact Of Malicious Nodes Corresponding To the Total Node Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was found that the localization error value decreased when we used the secure algorithm because of the authenticating mechanism used in the algorithm. Furthermore, the error value in the case of the basic DV-Hop was high in all cases compared to other algorithms, due to the usage of a distance error correction factor in the other algorithms [39]. Table 9 shows the average localization error variation corresponding to the total node number with and without malicious nodes for the proposed algorithm and other variants.…”
Section: Impact Of Malicious Nodes Corresponding To the Total Node Numbermentioning
confidence: 99%
“…They pointed out that some disturbances in measurements are observed on account of the RSS deviation due to the signal usage. Similarly, some recent work to take care of the issues pertaining to the node count and hop count has been addressed by the authors [39], where they provided an approach based on a virtual partitioning, along with its integration with the distance error concept to reduce the overall error. This scheme also proved beneficial apart from the other similar approaches.…”
mentioning
confidence: 99%
“…In [19], an NL method for WSNs that depends on virtual partition and distance correction (VPDC) was developed. Primarily, the distance of every hop on a shorter transmission path between the UN and beacon node is considered through the VP approach; next, the shorter communication path length was acquired by including every hop distance; at last, the distance among nodes was accomplished using the optimum path search method and the DC procedure.…”
Section: Related Workmentioning
confidence: 99%
“…The geographical distance to neighbors is then estimated through collaborative exchange and, finally, the bounding box is used to refine localization result. The node localization algorithm presented in [48] is based on virtual partition and distance correction. Each hop distance on the shortest path between the sensor node and the anchor node is estimated.…”
Section: Han Et Al Have Proposed In [43] a Mobile Anchor-based Locali...mentioning
confidence: 99%